A tool for assessing sexual knowledge of people with Intellectual disabilities in Norway - Svae, Gøril Brevik; Zachariassen, Peter; Fjeld, Wenche; Søndenaa, Erik (Frontiers in Psychiatry, 2024)
Background: Previous research has shown that people with intellectual disabilities have limited sexual knowledge, which can be essential for developing positive sexuality. This study aimed to check the validity and reliability of an assessment tool (SexKunn) for measuring the sexual knowledge of people with intellectual disabilities in Norway. Further, we aimed to identify potential knowledge gaps among the participants and highlight their potential impact.Methods: 37 people with intellectual disabilities completed one assessment. 20 participants then completed a retest. Clinicians' (n=23) views on the assessment tool were measured to obtain face validity. Positive and negative agreement analysis was used to identify potential dimensions in the data.A weighted Cohen's kappa for the test and retest of the overall scores was considered to be substantial. The clinicians described an acceptable face validity regarding high positive value scores and low negative burden scores. They also suggested improvements. The study identified that the participants lacked knowledge about female genitals, hygiene, appropriate touching/sexual acts with friends/ intimate partners, and contraception.The SexKunn is a feasible assessment tool to measure sexual knowledge in people with intellectual disabilities. A lack of sexual knowledge of people with intellectual disabilities may violate their sexual rights.